The Impact Of Artificial Intelligence Integration On Students’ Critical Thinking And Problem-Solving Skills In Higher Education - Sopacua, Fryan; Apra Santosa, Tomi; Aprianto, Muhammad Chusnan; Dewanto, Dewanto; Safira, Ifa; Wijoyo, Hadion (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
The rapid advancement of Artificial Intelligence (AI) has significantly transformed the educational landscape, particularly in higher education. This study aims to investigate the impact of AI integration on students’ critical thinking and problem-solving skills through a meta-analysis approach. Data were collected from 12 empirical studies published between 2015 and 2025 that examined the implementation of AI-assisted learning environments in universities. Using a random-effects model, the study analyzed effect sizes to determine the overall impact of AI-based interventions. The results reveal a moderate to strong positive effect (Hedges’ g = 0.64) of AI integration on critical thinking skills, and a significant improvement in problem-solving. Subgroup analysis further indicates that adaptive learning systems and AI-driven feedback tools produce the greatest enhancement in cognitive performance compared to traditional instruction. Moreover, the effectiveness of AI integration is influenced by factors such as duration of implementation, discipline area, and the level of technological literacy among students and instructors. These findings underscore the potential of AI as a transformative pedagogical tool that fosters higher-order thinking and learner autonomy in higher education. The study concludes by recommending that universities adopt AI technologies strategically, emphasizing instructional design that aligns with cognitive development principles to ensure sustainable and equitable learning outcomes.